Hazing in the U.S. Armed Forces Recommendations for Hazing Prevention Policy and Practice - Keller, Kirsten M. (RAND Corporation, 2015)
This report documents research focused on helping the Department of Defense build a more-systematic approach to hazing prevention and response. The report documents theory and research on the root causes of hazing and findings and recommendations regarding how best to define hazing, practices to prevent and respond to incidents of hazing, and how the armed forces can improve the tracking of hazing incidents.